Aeromycoflora of Jizan , Saudi Arabia . - Syeda Fatima Manzelat (EQA, 2017)
This is the first study to isolate and identify the  aeromycoflora of Jizan province . The study was carried out to estimate  quantitatively and qualitatively the mycoflora present in the air of different sampling sites of the province. Open petri plate method with Potato Dextrose agar media  was used  with an exposure time of 2 mins at each of the seven sampling sites. Total number of eight genera were isolated from the seven indoor and outdoor sampling sites of the province represented by   Aspergillus niger, Aspergillus sp. , Chaetomium ,Cladosporium, Nigrospora,Penicillium , Rhodotorula , Scedosporium and Ulocladium.  Seventy two  fungal isolates were obtained from the eight  represented genera . Aspergillus was the predominant genera.The Colony forming unit  (CFU)3  was calculated for all of the sampling sites under study to know the level of contamination .The high wind speed  and the busy hours of business were the major factors  responsible for large number of fungal counts during this study from the province.